Distributions, sobolev spaces, elliptic equations - Haroske, Dorothee D. (European Mathematical Society, 2008)
It is the main aim of this book to develop at an accessible, moderate level an L[subscript 2] theory for elliptic differential operators of second order on bounded smooth domains in Euclidean n-space, including a priori estimates for boundary-value problems in terms of (fractional) Sobolev spaces on domains and on their boundaries, together with a related spectral theory." "The presentation is preceded by an introduction to the classical theory for the Laplace-Poisson equation, and some chapters providing required ingredients such as the theory of distributions, Sobolev spaces and the spectral theory in Hilbert spaces